Bharathiyar's Patriotism and Ethnic Conflict Solutions - Shifa (International Research Journal of Tamil, 2022)
Caste has existed since ancient times till today. It can be understood that the origin of caste cruelty was the primary reason for the emergence of the race of ruler and slave on the basis of possession of the land. After that, there was discrimination between superiors and inferiors, and there was division among people in the name of caste and race. Both of them danced wildly, like uncontrollable demons. The land looks like a battlefield. People should live according to the guidance of these wise men so that conflicts and struggles disappear. Mahakavi Bharathi felt sorry for the religious and ethnic conflicts and differences that occurred in many parts of the world during his lifetime. All people should realize the greatness of mankind and live together as brothers and sisters. It was Bharathi's desire to see a peaceful country where people lived in harmony with freedom without conflict and with the resources provided by nature, their thoughts and wealth in the Indian society that was enslaved and divided.Mahakavi Subramania Bharathiyar was one of the many fighters who wanted to put an end to the abolition of caste. His creations are the earthquake that erupted in the mind that shattered caste and ethnicity. The purpose of this article is to show that through his poetry and articles, he pointed out the religious and ethnic struggles and showed the way to recover from them that was relevant to this era.